NILAI-NILAI PENDIDIKAN KARAKTER PADA TOKOH ALNAIRA MALIKA JANNAH DALAM NOVEL DEAR ALLAH KARYA DIANA - Erlina Zahar; Ram Novi Sardila (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study analyzed one type of literary work, the novel. This research aims to describe the values of character education in the character of Alnaira Malika Jannah in the novel Dear Allah by Diana Febi (Content Analysis). The research uses a qualitative descriptive type of research. The data collected from quotations related to aspects of character education values in the figure Alnaira Malika Jannah is further tabulated into the table of tabulation data. The next step is to analyze the data that has been collected following the theoretical foundation used with structural approaches and content analysis. Based on the results of the data analysis, it is known that the character Of Alnaira Malika Jannah in the novel Dear Allah has nine aspects of character education value which includes aspects of honest value as many as 12 citations, aspects of bold values are drawn as many as four citations, aspects of trust values are drawn as many as eight citations, aspects of wise values are drawn as many as one quote,  Aspects of shame value are illustrated as many as 29 citations, aspects of affection value are described as many as eight citations. Aspects of beautiful values are illustrated in as many as five citations. The total of the whole is 82 citations. The most dominant aspect of character education value is found in the value aspect of shame, while the minor aspect of value is the value aspect of wise.Keywords: value, educational character, character, novel, content analysis